Economic impact of recurrent respiratory papillomas in a UK adult population. Issue 7 (18th May 2016) - Harrison, A; Montgomery, J; Macgregor, F B
Abstract: Objective: To calculate the financial burden of recurrent respiratory papilloma. This study is UK-based, where up until now no financial estimates have been calculated for this group of patients. Background: Recurrent respiratory papilloma is caused by the human papilloma virus (subtypes 6 and 11). The burden for the patient and the healthcare system is significant given the recurrent nature of the disease. Methods: Data were collected, using a questionnaire completed during routine clinical follow up, from a single centre managing recurrent respiratory papilloma in Glasgow, Scotland. Cost information was sourced from the Scottish Government's Information Services Division. Results: Fourteen patients with active recurrent respiratory papilloma between 2013 and 2014 were identified. The direct measurable cost to NHS Greater Glasgow and Clyde amounted to £107 478. Conclusion: Recurrent respiratory papilloma is a benign condition, but the financial implications of diagnosis are significant. Recurrent respiratory papilloma has a natural history of relapse and remission, and patients may require healthcare input over a period of several years.